Deterring lone wolf terrorism in Singapore : the imperative for social interdiction - Chua, Kevin Peng Hock (2015)
Since occurrence of Lone Wolf terrorist attacks in Fort Hood and Oslo, Self-Radicalised Lone Wolf Terrorists have emerged as a clear and present threat in the global security landscape. In Singapore, with the arrest of six self-radicalised Individuals, the Singapore government has securitised the Lone Wolf terrorist threat. However, much have yet to be done to comprehensively deter this emerging terrorist threat. This dissertation would assert that the Lone Wolf Terrorist threat requires a comprehensive framework of deterrence and would require a whole-of-society approach to interdict the Lone Wolf Terrorist Threat.